2018
DOI: 10.1016/j.jtho.2018.10.135
|View full text |Cite
|
Sign up to set email alerts
|

P109 Combined Chemotherapy Versus Topotecan Monotherapy as Second-Line Treatment for Patients with Sensitive Relapsed SCLC

Abstract: Background: Cisplatin, etoposide and irinotecan are primary drugs in the treatment of small cell lung cancer. We did this retrospective study to investigate whether combined chemotherapy with cisplatin, etoposide, and irinotecan was better than topotecan alone as second-line chemotherapy in patients with sensitive relapsed SCLC. Method: Between 1st Sep, 2014 and 30th Sep, 2017,We collected the patients information in Jilin Province Cancer Hospital. All patients with SCLC responded in first-line treatment and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Seventeen studies (21,23,24,28,40,(61)(62)(63)(64)(65)(66)(67)(68)(69)(70) reported on the treatment of SCLC patients beyond first-line treatment. Patients were either retreated with their first- (40).…”
Section: Treatment Patterns: Relapsed/refractory Diseasementioning
confidence: 99%
“…Seventeen studies (21,23,24,28,40,(61)(62)(63)(64)(65)(66)(67)(68)(69)(70) reported on the treatment of SCLC patients beyond first-line treatment. Patients were either retreated with their first- (40).…”
Section: Treatment Patterns: Relapsed/refractory Diseasementioning
confidence: 99%